A Community Based Study on Various Aspects of Breast-Feeding Practices from Central India - Silawat, Sanjay; Verma, Vijay; Yuwane, Praveen; Dixit, Shivam (Journal of Pharmacy Practice and Community Medicine)
Background: For optimum growth and development of new-borns breastfeeding is of utmost importance. Identification of breastfeeding practise gaps need to be identified and filled. Objectives: This study was undertaken to explore the breastfeeding practices, influence of literacy and prevailing cultural factors on different aspects of breastfeeding. Materials and Methods: Complete line listing of 576 breastfeeding women in the study area was done. Then the study subjects were interviewed by making house to house visits. Data was gathered on the participant’s demographics, breastfeeding knowledge, and practices. Privacy was maintained while conducting the interview. Anonymity and confidentiality were ensured to the study participants. Results: Data of 550 study participants was analyzed and presented here. 377 (68.5%) could not practice timely initiation of breast feeding. Most common reason (264, 70%) for the same was insufficient knowledge about it. Exclusive breast feeding was practiced by merely 44 (8%) subjects. Not good for health of new-born (108, 36.7%), not easily digested by the new-born (thick) (85, 28.9%) and myths prevalent in society (64, 21.8%) were three most common reasons for discarding colostrum by mothers. Lower socio-economic status, muslim religion and joint family were found to be associated with practice of exclusive breastfeeding. Conclusion: The issue of lower prevalence of early breastfeeding initiation and exclusive breastfeeding continues to persist in the study area. Still, colostrum is being discarded. Tailored and region-specific health promotion activities must be intensified in this regard by grass root level health care workers.
Keywords: Breastfeeding; Colostrum; Cultural factors; Practice